The Relationship Between Family Support and Social Concern of Adolescents in Jorong Pondok, Sasak Ranah Pasisie sub-district, West Pasaman Regency - Wahyuni, Nira; Natsir, MHD (Universitas Negeri Padang, 2025)
This study originates from the phenomenon of low levels of social concern among adolescents in Jorong Pondok, Sasak Ranah Pasisie District, West Pasaman Regency. The lack of social concern is presumed to be influenced by family support. The purpose of this research is to identify whether there is a correlation between family support and adolescents’ social concern in the area. The study employed a quantitative approach with a correlational design. The population consisted of all adolescents aged 12–20 years residing in Jorong Pondok, totaling 102 individuals. The sample was determined using stratified random sampling, comprising 50% of the population, namely 51 respondents. Data were collected through questionnaires and analyzed using percentages and the product-moment correlation test. The findings revealed that: (1) the level of family support received by adolescents in Jorong Pondok was relatively low; (2) the level of social concern among adolescents in the area was also low; and (3) there was a significant relationship between family support and adolescents’ social concern in Jorong Pondok, Sasak Ranah Pasisie District, West Pasaman Regency.